Simulation of travel document purchase measures aimed at preventing the spread of COVID-19 – Case study from Slovakia - Zdenka Bulková; Juraj Čamaj; Adrián Šperka; Simona Jursová (Transportation Research Interdisciplinary Perspectives, 2023)
The COVID-19 pandemic has had a significant impact on railway services, such as restrictions on transport services, introduction of strict anti-pandemic measures at railway stations, and a ban on free travel. This study simulated passenger flow at the Bratislava railway station before and during the COVID-19 pandemic. This study provides an overview of the number of tickets sold, average waiting time of passengers, and time spent by passengers at ticket windows during peak and off-peak hours. The mass-service theory was used as the operational research method. In addition, the user interface of the AnyLogic simulation programme and practical results of the passenger flow simulations at the Bratislava railway station are discussed. The simulation results showed that passenger movement at the railway station was neither synchronised nor systematic. This concurred with the measures implemented during the pandemic that were considered unacceptable. New methods for selling travel documents at Slovak railway stations were proposed, which contribute to better spatial organisation of the stations, faster customer service at ticket windows, and negating infection risks.